Does Feedback Seeking Help Safety Performance Improvement? The Role of Consideration of Future Consequence - Zhang, Tian-tian; Li, Miao-miao (Frontiers in Psychology, 2021)
The purpose of this paper is to examine how feedback seeking impact safety performance through feedback environment and the moderating role of consideration of future consequence. Correlation data were collected from 202 participants in three industries of China. Results indicate that feedback seeking is positively associated with feedback environment and safety performance, the feedback environment mediated the relationship between feedback seeking and safety performance. However, the positive effect of feedback environment on safety performance is more significant when consideration of future consequence is high. Overall, the findings highlight the critical importance of individual features in the research on safety performance. The conclusion is conducive to a more detailed understanding of the antecedents that affect safety performance and provides a new perspective for the improvement of safety performance.